Comparison of Moderate Blockage of Left Main Stem (LMS) Assessment on Catheter Angiography Versus Coronary Computed Tomographic Angiography (Medical Forum Monthly, 2022)
Objective: To assess the diagnostic ability of non-invasive computed tomographic angiography (CTA) against invasive catheter angiography (ICA) in patients with moderate left main stem (LMS) (40-49%).Study Design: Prospective Comparative StudyPlace and Duration of Study: This study was conducted at the cardiology department of Ch. Pervaiz Elahi Institute of Cardiology Multan for one year from July 2020 to July 2021.Materials and Methods: Computed tomography angiography (CTA) and invasive catheter angiography (ICA) were performed in 45 coronary lesions with moderate severity. Percent diameter stenosis (%DS) and Minimal lumen diameter (MLD) were assessed by ICA and CTA. Inducible ischemia was determined by fractional flow reserve (FFR) value less than 0.80. The diagnostic value of the two methods was compared.Results: 8 (20%) lesions had FFR ≤0.80. Mean CTA MLD was found to be lower than mean ICA MLA (1.3 ± 0.5 vs. 1.5 ± 0.5 mm, P < 0.001). Similarly, mean CTA %DS was higher than ICA %DS (53.5% ± 14% vs. 49.8% ± 11.8%, P < 0.001). These findings remained independent of the location of the lesion, its severity, and its plaque nature. In terms of ischemia prediction, diagnostic value of CTA %DS was less than that of ICA %DS (P = 0.04).Conclusion: Invasive and non-invasive methods vary by diagnostic criteria in terms of the detection of ischemia-producing coronary stenosis. Compared with ICA, CTA overestimates lesion severity and has a lesser diagnostic capacity to assess ischemia.